Prevalence of rickets: a clinical study - Reddy, K. Ashwin (International Journal of Contemporary Pediatrics, 2020)
Background: Rickets is a growing bone disease that is common in children and adolescents. It is triggered by the inability of the osteoid to calcify in a growing individual. Even in countries with ample sun exposure, rickets is a common health problem which leads to frequent morbidities. Inadequate information on its prevalence and risk factors is available. For the study of prevalence and prominence of clinical characteristics of rickets in children aged between 0 - 10 years. Methods: The present research was a cross-sectional analysis. This study was conducted over a period of one year from June 2018 to June 2019. Department of Pediatrics, Malla Reddy Medical College, Hyderabad, India. This prospective study was conducted on 100 children presenting with signs of rickets in the pediatric department of Malla Reddy Medical College, Hyderabad. The detailed history thorough clinical examination, anthropometric measurements and ratios of each child enrolled in the study was taken. The social and demographic data was also obtained through a structured questionnaire. Results: The prevalence of rickets was found to be more prevalent in males with (70%) than in females (30%). Rickets prevalence was around 46% in the study which is higher compared to other studies. Most of the cases around 85% belonged to the age group of 0-5 years. Rachitic rosaries were the most prominent sign amongst all. Conclusions: Because of its greater prevalence among infants, Rickets continue to be a major health problem. Rachitic rosaries and thickened epiphysis are the most common clinical signs. Since Rickets are a disease which can be prevented, vitamin D should be supplemented.